How is feedback from national clinical audits used? Views from English National Health Service trust audit leads. (April 2016) - Taylor, Angelina; Neuburger, Jenny; Walker, Kate; Cromwell, David; Groene, Oliver
Objective: To explore how the output of national clinical audits in England is used by professionals and whether and how their impact could be enhanced. Methods: A mixed-methods study with the primary recipients of four national clinical audits of cancer care of 607 local audit leads, 274 (45%) completed a questionnaire and 32 participated in an interview. Our questions focused on how the audits were used and whether barriers existed to using the audits for local service improvement. We described variation in questionnaire responses between the audits using chi-squared tests. Results are reported as percentages with their 95% confidence intervals. Qualitative data were analysed using Framework analysis. Results: More than 90% of survey respondents believed that the audit findings were relevant to their clinical work, and interviewees described how they used the audits for a range of purposes. Forty-two percent of survey respondents said they had changed their clinical practice, and 56% had implemented service improvements in response to the audits. The degree of change differed between the four audits, evident in both the questionnaire and the interview data. In the interviews, two recurring barriers emerged: (1) the importance of data quality, which, in turn, influenced the perceived relevance and validity of the audit data and therefore the ability to make changes based on it and (2) the need for clear presentation of benchmarked local performance data. The perceived authority and credibility of the professional bodies supporting the audits was a key factor underpinning the use of the audit findings. Conclusion: National cancer audit and feedback is used to improve services, but their impact could be enhanced by improving the data quality and relevance of feedback.